Pneumonia associated with mechanical ventilation (Research, Society and Development, 2023)
Introduction: Ventilator-associated pneumonia is one of the main infections related to health care, it occurs due to the prolonged use of an endotracheal tube in mechanical ventilation, and manifests itself with a time greater than 48 hours after intubation and/or 72 hours after intubation. extubation, along with other risk factors. Objective: To define the relationship between mechanical ventilation and pneumonia. Methodology: This is an integrative review, with articles describing the relationship between mechanical ventilation and pneumonia and its risk factors, from 2016 to 2022. Results: From the records in the databases, 16,600 articles were retrieved, the Based on inclusion and exclusion criteria, 8,990 remained. In order to meet the proposed objective, the titles and abstracts were carefully read, resulting in the selection of 21 articles, leaving only 9 in the final sample. Thus, such studies were applicable in providing information on the relationship between mechanical ventilation and pneumonia. Final Considerations: This study showed that pneumonia associated with mechanical ventilation is a significant cause of morbidity and mortality in critically ill patients in intensive care units undergoing invasive mechanical ventilation. Thus, preventive nursing actions and measures are extremely important, as it is the nursing team that has great responsibility for preventing complications and complying with protocols.